2021
DOI: 10.48550/arxiv.2102.07350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prompt Programming for Large Language Models: Beyond the Few-Shot Paradigm

Abstract: Prevailing methods for mapping large generative language models to supervised tasks may fail to sufficiently probe models' novel capabilities. Using GPT-3 as a case study, we show that 0-shot prompts can significantly outperform few-shot prompts. We suggest that the function of few-shot examples in these cases is better described as locating an already learned task rather than meta-learning. This analysis motivates rethinking the role of prompts in controlling and evaluating powerful language models. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…For instance placing "TL;DR" (internet slang for Too Long; Didn't Read) at the end of an article causes the model to generate a summary. Efficiently discovering the right prompt is difficult and has become an active area of research (Reynolds and McDonell, 2021;Shin et al, 2020;Jiang et al, 2020). Brown et al (2020) demonstrated that few-shot learning without fine-tuning is possible with very large language models.…”
Section: Background and Related Workmentioning
confidence: 99%
“…For instance placing "TL;DR" (internet slang for Too Long; Didn't Read) at the end of an article causes the model to generate a summary. Efficiently discovering the right prompt is difficult and has become an active area of research (Reynolds and McDonell, 2021;Shin et al, 2020;Jiang et al, 2020). Brown et al (2020) demonstrated that few-shot learning without fine-tuning is possible with very large language models.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Prompt-based approaches involve constructing optimal prompts for language models to best elicit knowledge and maximize prediction performances (Radford et al, 2019;Schick and Schütze, 2020). As the scale of language models grows, the potential of replacing the full finetuning paradigm with the prompt-based approach has been reported (Reynolds and McDonell, 2021;Li and Liang, 2021), as learning via prompts is efficient regarding time and space complexity. However, language models are highly sensitive to the prompt design, motivating methodologies for optimizing prompts.…”
Section: Prompt Optimizationmentioning
confidence: 99%
“…It has been shown that a well-selected prefix, or 'prompt', can dramatically increase the performance of a language model on a specific task [41]. A resulting line of research has been automatically creating either natural language prompts or continuous vector prompts, to perform well on tasks [19,34].…”
Section: Natural Language Generationmentioning
confidence: 99%
“…First we craft a 'prefix' prompt to pre-pend to any prompt used by a writer. Prefix prompts have been shown to greatly improve performance by providing the language model with appropriate context [41]. We found early on in development that simply providing the model with a technical topic was not enough -also providing a context area was necessary for it to appropriately interpret technical terms.…”
Section: Design Goalsmentioning
confidence: 99%